Health Benefits of Mango By-products - Abraham, Wall-Medrano (Wiley Blackwell, 2020)
Nearly half of all tropical fruits produced worldwide are mangoes (Mangifera indica L.) and their net production is expected to grow steadily in the next two decades; this is a result of improved agro-industrial methods, the marketing of new varieties, and their demand by health-conscious consumers. However, during their agronomic-to-industrial processing, vast amounts of nonedible wastes (e.g. leaves and barks) and by-products (e.g. peels, seeds, and bagasse) are generated, not only causing significant environmental impact but also economic losses. Conventional recovery methods offer eco-friendly solutions (e.g. soil bioremediation and livestock feeding) but novel technologies are more profitable, sustaining their continuous growth on the fact that many mango phytochemicals can be recovered from these industrial residues for the cosmetic, food, and nutraceutical industries. For instance, mango peel and bagasse are rich sources of dietary fiber (pectin/cellulose), carotenoids, and phenolic compounds with proven benefits for cardiovascular, type 2 diabetes, metabolic syndrome, and cancer, while mango seed is a rich source of vegetable oil (stearic/oleic), proteins, and macromolecular antioxidants with antibiotic potential. In this chapter, we review the nutritional and functional value of mango by-products, their bio-efficacy, and related nutraceutical mechanisms.